Implementasi Program Penerangan Jalan Umum (PJU) Oleh Dinas Lingkungan Hidup Kabupaten Pulau Morotai - Dominggus, Idhan; Sumai, Saiful (Peneliti.net, 2026)
This study aims to determine the extent of the implementation of the Public Street Lighting (PJU) program carried out by the Environmental Service of Morotai Island Regency. The research technique used is a qualitative descriptive method approach, where the data collection process in this study includes observation, interviews, and documentation. The results of the study indicate that the implementation of the public street lighting (PJU) program carried out by the Environmental Service of Morotai Island Regency has not been implemented optimally. Although the planning stages have been carried out through Musrenbang and the preparation of Detailed Engineering Design (DED), the lack of budget causes physical activities such as identification of needs, technical planning, budgeting, procurement, and installation cannot be realized. In implementing the public street lighting program, the Environmental Service of Morotai Island Regency experiences obstacles, these obstacles are changes in budgeting policies and reallocation of funds causing all public street lighting implementation activities to not run optimally..